DETERMINATION OF THE INFLUENCE OF THE FILLER INTRODUCTION METHOD ON THE PROPERTIES OF POLYETHYLENE FILMS - РОЗВОРА, Любомир; СЛЄПЦОВ, Олександр; САВЧЕНКО, Богдан; СОВА, Надія; САВЧУК, Богдан (Technologies and Engineering, 2025)
Purpose. Determine the effect of the method of introducing a mineral filler based on calcium carbonate on the mechanical properties of polyethylene films and to determine the most effective technological approach to their manufacture. Methodology. The methods of literature and systematic analysis of scientific publications on the subject of the study were used to summarize the existing data and choose the direction of research. The mechanical properties of the studied film samples were determined according to DSTU EN ISO 527-3:2017. Findings. The article is devoted to the study of the influence of the filler introduction method on the properties of polyethylene films based on linear polyethylene and low-density polyethylene. In the course of the research, prototypes of polyethylene films containing a filler based on natural calcium carbonate in the amount of 10–50% by weight were obtained. Two technologies were used to introduce the filler: introduction through the compound and concentrate. The analysis of the results of the study of the mechanical properties of the obtained films showed that the technology of filler introduction through the compound allows to obtain films with higher mechanical properties for both types of polymers. This is probably due to a more uniform distribution of the filler in the volume of the polymer matrix Originality. It has been established that the mechanical properties of polyethylene films depend on the method of introducing the filler into their structure. The introduction of the filler by the compound method in the amount of 50% by weight allows for a 1.5-fold increase in the value of relative elongation at break and a 1.9-fold increase in tensile strength compared to the method of introduction by using a concentrate. Practical value. A technology for introducing filler into polyethylene films by the compound method is proposed, which provides a higher level of mechanical properties compared to the method of introducing concentrate.